Integration of Torah and Ecotheology: Strengthening the Social Forestry System in Indonesia - Wibowo, Gandi; Wiley, Robert W. (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Indonesia is grappling with the complex challenge of managing its forests in a truly sustainable way. Problems such as land degradation, widening socio-economic gaps, and ongoing environmental damage not only threaten the well-being of local communities but also put at risk the country’s rich biodiversity that is vital to the world. Although social forestry programs in Indonesia hold tremendous promise, their implementation often overlooks the integration of traditional ecological wisdom and theological perspectives—elements that could enrich and strengthen current forest management practices. This study proposes the integration of principles from the Torah, emphasizing stewardship, biodiversity preservation, and justice, along with insights from ecotheology, to inform sustainable social forestry management in Indonesia. Drawing on religious texts, theological insights, and contemporary environmental scholarship, this research explores how the teachings of the Torah and ecotheological perspectives can be applied to enhance social forestry practices. Case studies from Israel, along with initiatives led by Catholic and Protestant churches in Indonesia, demonstrate how religious values can be woven into environmental conservation. By integrating Torah principles and ecotheological perspectives into social forestry, forest management can evolve into a more holistic practice—one that not only protects the environment but also nurtures social cohesion and spiritual well-being. Applying these principles paves the way for sustainable forestry in Indonesia, while at the same time uplifting local communities and safeguarding nature for future generations.